ANALISIS ANALISIS KEPUASAN WAJIB PAJAK TERHADAP PELAYANAN SAMSAT LUBUK PAKAM - Mustapa, Juang; Lubis, Tukimin (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2021)
This research is a field research located at the SAMSAT Lubuk Pakam Office, Deli Serdang Regency. The data collection instrument in this study was through observation, interviews and documentation. While the data analysis used by the author consists of data reduction (data reduction), data presentation (data display) and drawing conclusions (verification). This research is about public complaints about the provision of SAMSAT Lubuk Pakam services, including the lack of an unbalanced number of apparatus (public servants) with the community, the absence of a service queue serial number, the lack of parking space, the open space is not closed, not air conditioned, mineral water is not provided. in the waiting room, the waiting room is too narrow, there is no glass divider for services and there are no wifi and TV facilities so that those who pay taxes don't get bored waiting. Because the number of people who pay with the number of apparatus (public services) is not balanced. From the results of the research, the reliability and guarantees provided by the SAMSAT officers were considered very good by the taxpayers and in accordance with the expectations of the taxpayers, so that the taxpayers were satisfied with the services of the SAMSAT officers. Efforts made by SAMSAT Lubuk Pakam to obtain service quality in increasing taxpayer satisfaction include improving services through information technology, providing mobile SAMSAT services (cars), increasing professional human resources and providing optimal services, improving service facilities so that excellence is achieved. , providing counseling and socialization about motor vehicle tax to taxpayers at both the sub-district and district levels.